Reproductive biology and pollination of the carnivorous Genlisea violacea (Lentibulariaceae) - Aranguren, Y. [UNESP]; Płachno, B. J.; Stpiczyńska, M.; Miranda, V. F.O. [UNESP] (Wiley, 2018)
Genlisea violacea is a Brazilian endemic carnivorous plant species distributed in the cerrado biome, mainly in humid environments, on sandy and oligotrophic soil or wet rocks. Studies on reproductive biology or pollination in the Lentibulariaceae are notably scarce; regarding the genus Genlisea, the current study is the first to show systematic and standardised research on reproductive biology from field studies to describe the foraging of visiting insects and determine the effective pollinators of Genlisea. We studied two populations of G. violacea through the observation of flower visitors for 4 months of the rainy and dry seasons. Stigmatic receptivity, pollen viability, and breeding system were evaluated together with histochemistry and morphological analyses of flowers. The flowers showed stigmatic receptivity of 100% in open buds and mature flowers, reducing to 80% for senescent flowers. Nearly 80% of pollen grains are viable, decreasing to 40–45% after 48 h. Nectar is produced by glandular trichomes inside the spur. Two bee species are effective pollinators: one of the genus Lasioglossum (subgenus Dialictus: Halictidae) and the other of the genus Ceratina (subgenus Ceratinula: family Apidae). Moreover, bee-like flies of the Syrphidae family may also be additional pollinators. Genlisea violacea is an allogamous and self-compatible species. The differences in flower-visiting fauna for both populations can be attributed to factors such as climate, anthropogenic effect, seasonal factors related to insects and plants, as well as the morphological variation of flowers in both populations.
Keywords: Bee; carnivorous plant; floral biology; floral micromorphology; Genlisea; Lentibulariaceae; pollination